Endoscopic papillectomy for laterally spreading lesions of the papilla: a propensity score-matched analysis - Vu Trung, Kien; Abou-Ali, Einas; Gulla, Aiste; Soares, Kevin; Caillol, Fabrice; Paik, Woo H.; Napoleon, Bertrand; Halimi, Asif; Masaryk, Viliam; Bruno, Marco J.; Pérez-Cuadrado-Robles, Enrique; Bolm, Louisa; et al. (Endoscopy, 2025)
Endoscopic papillectomy is a standard treatment for ampullary lesions, which are typically small and confined to the papillary mound. Laterally spreading lesions (LSLs) of the papilla of Vater are a rare ampullary lesion subtype involving extensive duodenal mucosa. Data on endoscopic papillectomy outcomes for LSLs are limited. This study compared endoscopic papillectomy for ampullary LSLs and non-LSLs in matched cohorts. The ESAP study (Endoscopic papillectomy vs. Surgical Ampullectomy vs. Pancreaticoduodenectomy for ampullary neoplasm) encompassed 1422 endoscopic papillectomies. Propensity score matching used the nearest-neighbor method for age, sex, co-morbidity, and histologic subtype as cofactors. The main outcomes were complete resection (R0), technical success, complications, and recurrences. Propensity score-based matching identified 232 patients with ampullary lesions (116 non-LSL, 116 LSL) with comparable baseline characteristics. After first intervention, the R0 resection rate, the primary outcome measure, was significantly lower in the LSL group (54.3% [95%CI 45.3%-63.1%]) vs. 69.0% [95%CI 60.4%-76.6%]). Following repeated endoscopic interventions, technical success was similar in both groups (82.8%). After a 22-month median follow-up, the LSL group had significantly more recurrences (41.3% vs. 15.0%) and lower 1- and 3-year disease-free survival rates (61.1% and 44.0% vs. 86.1% and 81.6%, respectively). Complication rates did not differ significantly between the two groups (LSL 32.8% vs. non-LSL 26.7%). LSLs can be safely resected by endoscopic papillectomy, although repeated interventions are necessary to achieve complete resection. The higher risk of recurrence in LSLs necessitates a vigilant surveillance strategy.